Basophils are recruited to inflamed lungs and exacerbate memory Th2 responses in mice and humans. Issue 2 (4th December 2012) - Wakahara, K.; Van, V. Q.; Baba, N.; Bégin, P.; Rubio, M.; Delespesse, G.; Sarfati, M.
Abstract Background Although the contribution of basophils as inducers or amplifiers of Th2 responses is still debated, prolonged basophil/CD4 T cell interactions were observed in lungs but not lymph nodes (LNs) of parasite‐infected mice. However, the impact of basophils on the function of tissue CD4 effector T cells remains unknown. Methods Basophils were purified from the lungs of ovalbumin (OVA)‐sensitized and OVA‐challenged (OVA‐immunized) mice or human peripheral blood for in vivo and in vitro functional studies. Pulmonary basophils were adoptively transferred to OVA‐sensitized hosts to assess airway inflammation in bronchoalveolar lavage fluid (BALF) and Th2 responses in lung explants and draining LNs. Basophils were co‐cultured with effector T cells or Ag‐specific naïve T cells alone or in combination with dendritic cells (DCs); IL‐4 production was determined by flow cytometry and ELISA. Results Basophils accumulated in lungs of OVA‐immunized mice. Adoptive transfer of basophils to OVA‐sensitized hosts enhanced lung IL‐4 and IL‐13 release while co‐administration of OVA further aggravated airway inflammation and Th2 responses in LNs. Mechanistic in vitro studies revealed that pulmonary basophils interacted with lung CD4 effectors, in the absence of DCs, to increase T cell survival and Th2 cytokine expression at the single cell level but amplified OVA‐loaded DC‐driven Th2 differentiation. Finally, human basophils augmented in vitro IL‐4 expression in effector memory CD4 T cells that include CRTH2+ cells through IL‐4 and TCR‐independent pathways. Conclusions Basophils may worsen Th2 inflammatory disorders through direct interactions with pathogenic CD4 T cells as well as by enhancing DC‐induced Th2 cell development.